SCOURING-RUSH HORSETAIL’S (Equisetum hyemale) CAPABILITY TO REDUCE DETERGENT, COD AND PHOSPHAT (PO4) LEVELS OF LAUNDRY WASTEWATERIN PURWOKERTO IN 2016 - Hari Rudijanto Indro Wardono; Sugeng Abdullah; Zaeni Budiono (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: There will be an increasing demand for goods and services as a result of rapid economic growth and development, increasing activities in the society, and also with the establishment of universities. This has caused the emergence of some laundry business that aims to alleviate the burden on society. The emergence of the laundry business may cause environmental pollution, especially in the levels of detergent, if the waste generated is not treated before it is discharged. Therefore, it is necessary to find a method to treat waste efficiently. One of the ways is to employ phytoremediation using scouring-rush horsetail (Equisetum hyemale). Aims: The purpose of this study is to analyze the scouring-rush horsetail media’s ability in decreasing the levels of detergent, Phosphate (PO4), and COD of laundry waste. Methods: This type of research is called true experiment with design randomized control group pretest-posttest. The data is analyzed using Analysis of Covariance (ANCOVA) statistical test. Results: The results of the analysis showed that there are influences from the residence time, the scouring-rush horsetail’s (Equisetum hyemale) ability and the continuous process by reducing the levels of detergent (88.9%), COD (99.5%), and PO 4 (63.4%). Scouring-rush horsetail media has an average efficiency of COD reduction (90%), PO 4 (51%), and Detergents (86%). The value of Detergents, COD, and PO4 level in laundry wastewater after treatment by using scouring-rush horsetail (Equisetum hyemale) with a residence time (0 day, 1 day, 3 days and 7 days) based on Government Regulation No. 82 of 2001 on the Management of Water Quality and Water Pollution Control has been under NAB. Conclusion: It is necessary to make additional acclimatization time in the study using a scouring- rush horsetail to reduce the levels of COD, phosphate and detergent. It is advisable to plant the scouring-rush horsetail in the tub as high as 30 cm, thus the water can be pooled.